Tuning the Electrical Parameters of p-NiOx-Based Thin Film Transistors (TFTs) by Pulsed Laser Irradiation - Poreddy Manojreddy; Srikanth Itapu; Jammalamadaka Krishna Ravali; Selvendran Sakkarai (Condensed Matter, 2021)
We utilized laser irradiation as a potential technique in tuning the electrical performance of NiOx/SiO2 thin film transistors (TFTs). By optimizing the laser fluence and the number of laser pulses, the TFT performance was evaluated in terms of mobility, threshold voltage, on/off current ratio and subthreshold swing, all of which were derived from the transfer and output characteristics. The 500 laser pulses-irradiated NiOx/SiO2 TFT exhibited an enhanced mobility of 3 cm2/V-s from a value of 1.25 cm2/V-s for as-deposited NiOx/SiO2 TFT, subthreshold swing of 0.65 V/decade, on/off current ratio of 6.5 × 104 and threshold voltage of −12.2 V. The concentration of defect gap states as a result of light absorption processes explains the enhanced performance of laser-irradiated NiOx. Additionally, laser irradiation results in complex thermal and photo thermal changes, thus resulting in an enhanced electrical performance of the p-type NiOx/SiO2 TFT structure.